Mobilization of radical right movements in Central and Eastern Europe between 2008 and 2016 - Caiani, Manuela; Płatek, Daniel; Piotrowski, Grzegorz (Intersections. East European Journal of Society and Politics, 2024)
The radical right is on the rise all over Europe and beyond, either in terms of electoral success or activities outside the institutional arena, especially after the 2015 refugee crisis. Central and Eastern European countries are no exception, although not yet closely studied for radical right social movements and protest. In this article we investigate the degree and characteristics of the mobilisation of different types of radical right organisations (political parties and social movements alike) in Central and Eastern Europe to capture a broader picture of the current developments in radical right politics beyond elections and electoral campaign periods. By focusing on four countries (Czechia, Hungary, Poland and Slovakia), and combining qualitative and quantitative data derived from a protest event analysis reported in newspaper articles between 2008 and 2016 (for a total of 1587 events coded), we analyse the radical right mobilisation (i.e. intensity and degree of radicalism), linking it to the political opportunities and the organisational features of the groups mobilising. We argue that the radical right is using a very broad repertoire of action, beyond violence and the electoral arena, including expressive and symbolic strategies, as well as the use of new technologies like the Internet. We also stress that for the radical right, as for the left-wing social movements, the analytical framework of political opportunities and a resource mobilisation approach can help in explaining their mobilisation.